PROMOTING DESIGN THINKING AS A TECHNIQUE ON TEACHING SPEAKING SKILL - siti sa'diah; endah novita; nur latifah (Journal of English Language and Literature (JELL), 2018)
Speaking in English as a foreign language is highly complex and challenging skill for Indonesian students. It requires grammar, pronunciation, and vocabulary mastery. It also needs students’ confidence to be brave to share their ideas. This study attempted to promote design thinking that can be used on teaching speaking in order to stimulate the teachers to try to apply this technique on their teaching and to enhance their students’ speaking skill. In order to reach the objective of the study, the qualitative approach was used. Based on the analysis, it showed that the design thinking technique guides gradually the students to overcome the problem situationally and contextually by understanding, observing, pointing view, ideating, prototyping, and testing all ideas related to the problem in order to get the distintive and creative solution. In other words, the students are directed to think critically and brave to share their thoughts in a spoken language. So, the students can get more chance to speak them up and it, certainly, can help the students to increase their speaking skill